Navigating the frontier: Comprehensive insights into CRISPR technology advancements, delivery strategies, and ethical considerations in cancer research - Manisha S. Jain; K.S. Srikruthi; Prakash Goudanavar; N Raghavendra Naveen (Oral Oncology Reports)
This review article provides a thorough exploration of the multifaceted landscape surrounding CRISPR technology, with a specific focus on its evolution from genome editing to therapeutic applications in cancer research. Beginning with an overview of the principles underpinning CRISPR technology, the narrative unfolds to elucidate the intricate cellular pathways influenced by CRISPR. The review delves into the advancements that have propelled CRISPR to the forefront of molecular biology, detailing key elements and formats of the CRISPR/Cas9 system. A critical aspect of this review is the comprehensive analysis of CRISPR delivery strategies, encompassing transfection methods, common strategies, and the obstacles encountered in the process. The discussion extends to the burgeoning field of tumor research modeling using CRISPR, shedding light on its potential applications and challenges. Furthermore, the article explores the application of CRISPR/Cas9 gene editing to overcome cancer-mediated resistance and its potential role in drug delivery. A significant portion of the review is dedicated to the integration of nanotechnology with CRISPR for cancer treatment, discussing nanoparticle systems and their effectiveness in enhancing delivery precision. Addressing concerns related to CRISPR genome editing, the review examines off-target effects and underscores the importance of bioethical considerations in the implementation of CRISPR technology. The synthesis of information across these diverse domains contributes to a holistic understanding of CRISPR's current status, challenges, and promising avenues in cancer research and therapeutics.